PENGUATAN PRAKTIK IBADAH BAGI ANAK MIGRAN INDONESIA DI PKBM PNF KBRI KUALA LUMPUR - Muhammad Zidan Irfani; Siti Luluk Nafisah; Wahyuning Untari; Rendi Kurniawan; Qurroti A’yun; Shohenuddin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This activity aims to strengthen Indonesian migrant children’s understanding and practice of Islamic prayer (shalat) through structured and contextual religious education at PKBM PNF KBRI Kuala Lumpur. This community service activity was carried out using the Service Learning approach, with methods including demonstration, direct practice, and reflective debriefing. The activity was conducted on 6–9 October 2025, involving 42 students from grades V and VI. Data were collected through participatory observation, informal interviews, and activity documentation. The results showed that contextual mentoring through demonstration and repeated practice significantly improved students’ accuracy in performing prayer movements and recitations, as well as their self-confidence and religious awareness. This activity demonstrates that PKBM can serve as a primary center for spiritual formation and religious habituation for Indonesian migrant children abroad.